Seed Structural Variability and Germination Capacity in Passiflora edulis Sims f. edulis - Castillo, Nohra Rodríguez; Melgarejo, Luz Marina; Blair, Matthew Wohlgemuth (Frontiers in Plant Science, 2020)
Purple passion fruit, Passiflora edulis Sims f. edulis, is an important semi-perennial, fruit bearing vine originating in South America that produces a commercial tropical juice pulp for international and national consumption. Within the round purple passion fruit are a large number of membranous seed sacs each containing individual seeds. Little is known about the seed anatomy of the commercial passion fruit, differences between wild collected and commercial types and its effect on seedling germination. Therefore, our main objective for this study was to analyze the seed anatomy variability of different germplasm as well as the effect on viability and germination of the seeds of this species. Germplasm was evaluated from three sources: 1) commercial cultivars grown in current production areas 2) genebank accession from the national seed bank, and 3) landraces collected across different high and mid-elevation sites of the Andean region. A total of 12 morphometric descriptors related to seed anatomy were evaluated on the 58 genotypes, of which three were most informative: Angle to the vertex which is related to the shape of the seed, the thickness of the tegument and the horizontal length; separating the seed according to its source of origin. Germination was found to be positively correlated with the number and depth of seed pitting (foveas). Seeds of the commercial cultivars had more seed pits and higher germination compared to seeds of landraces or genebank accessions showing a possible effect of domestication on the crop. Interestingly, passion fruits often germinate during the rainy season as escaped or wild seedlings especially in the disturbed landscapes of coffee plantations, so some dormancy is needed but faster germination is needed for intensive cultivation. Harnessing passion fruit diversity would be useful as the semi-domesticated landraces have valuable adaptation characteristics to combine with rapid germination selected in the commercial cultivars. The variability of seed pitting with cultivars more fovaceous than landraces resulting in faster germination may indicate that purple passion fruit is still undergoing a process of selection and domestication for this trait.